Unveiling the Implementation of Bandung-Cuenca Sister City Relationship on Indonesian Cultural Diplomacy - Malik, Yusuf Idrus (Journal of Paradiplomacy and City Networks, 2023)
This qualitative study investigated the paradiplomatic engagement between Bandung, Indonesia, and Cuenca, Ecuador, to enhance the global recognition of Indonesian culture, with a special focus on Bandung's batik and traditional angklung music. Employing a descriptive methodology, this research drew on literature reviews, official governmental documents, and theories to underscore the nuanced dynamics of sister city collaborations in fostering cultural exchange and mutual understanding beyond conventional diplomatic channels. Findings indicated that the partnership had pioneered the creation of Ecuadorian-inspired batik designs and the international promotion of angklung and contributed to a broader dialogue on the world’s cultural preservation and innovation. However, challenges remain in achieving substantial advancements for strategic development. This study contributes to the understanding of how local governments can leverage cultural assets to strengthen international relationships, suggesting that the agreements serve as valuable platforms for cultural diplomacy and international outreach. Recommendations for enhancing the effectiveness of such partnerships include a greater emphasis on measurable outcomes and reciprocal cultural exchanges.